Anonimato e fama no reality show BBB 3 - Pinheiro, Mirian Moema (2005)
In the present work we make an incursion about the Reality Show, in a specific study of the program Big Brother 3 (BBB 3) approaching the question of Anonymity and Fame, though of its Narratives Strategic. We search to explain phenomenon of transformations of anonymous people in celebrities, showing all net of relationships established by the participants of BBB 3, during the together in the setting house, stage of the tram that tells the daily one of a group of youngs. Supported in concepts of it and Reality Show, the work is link the theories semiotic of means, proposal for Algirda Julien Greimas. We stand out strategies of the program, showing that they on the basis of structuralize elements fiction that stimulate and seduce the receiving public. How empirical reference, the work bases on the program Big Brother Brazil, shown for the Rede Globo de Televisão opened canal, in period of January 14 to April 01 of 2003. Ahead of the results gotten in analysis, we verify that BBB 3 is a format of reality and fiction. What although to create the effect of a hurt of real everything to show, its reality artificial, built principally for edition of the images